A Conceptual Model for the Development of Rural Territories of Regions Based on the Principles of Green Economy - Elena G. Kovalenko; Tatiana M. Polushkina; Olga Yu. Yakimova; Yulia A. Akimova (Регионология, 2022)
Introduction. In recent years in Russian theory and practice more and more attention has been paid to the transition to a green economy through the introduction of innovative clean technologies that ensure resource conservation and increased attention to environmental protection and biodiversity conservation. Rural territories of the country’s regions are significantly differentiated by all elements of sustainable development: economy, quality of life and the state of the environment. If the first two elements are actively promoted through the implementation of targeted programs and projects, then the preservation of natural potential, the prevention of environmental degradation by reducing its pollution is not being implemented enough. So, the purpose of the article is, on the basis of the study, to determine the priority areas for the introduction of green technologies in agriculture, contributing to the solution of environmental and social problems of administrative-territorial entities.